Significant Changes in the Diagnosis, Injury Severity and Treatment for Anterior Shoulder Instability Over Time in a U.S. Population - Devin P. Leland, M.D; Chad W. Parkes, M.D; Christopher D. Bernard, M.D; Aaron J. Krych, M.D; Diane L. Dahm, M.D; John M. Tokish, M.D; Christopher L. Camp, M.D (Elsevier, 2020)
Purpose: To report the annual incidence of anterior shoulder instability (ASI) diagnosis, injury severity, and surgical stabilization in a U.S. population. Methods: An established U.S. geographic database was used to identify patients < 40 years old with diagnoses of ASI from 1994-2016. Medical records were reviewed to obtain patient demographics, histories, imaging results, and surgical details. Age- and sex-specific incidence rates were calculated and adjusted to the 2010 U.S. population. Poisson regression was performed to examine trends by timeline, sex and age. Results: The study population consisted of 652 patients with ASI and a mean age of 21.5 years (range, 3.6-39.5). Comparing 2015-2016 to 1994-1999, we found an increase in the number of dislocations (from 1.0-1.9; P = 0.016) and total instability events (from 2.3-3.4; P = 0.041) per patient prior to presentation to a physician. There was a trend in increased diagnosis of bony Bankart and/or Hill-Sachs on MRI over time, with these lesions documented in 96% of patients undergoing MRI in 2015-2018 compared to 52.9% in 1994-1999 (P < .001). The use of arthroscopic procedures increased and peaked in 2005-2009 (90% of surgical cases performed). The proportion of open Latarjet procedures increased from 2010-2014 (14%) and 2015-2018 (31%). Conclusions: The age- and sex- adjusted incidence of ASI diagnosis in a U.S. population from 1994-2016 is comparable to that demonstrated in Canadian and European populations. This study demonstrates an increasing number of instability events prior to surgical evaluation, which may correlate with patients' more commonly presenting with bone loss and requiring more aggressive surgical treatment or that ASI is being more frequently cared for and documented by present-day orthopedic surgeons. Level of Evidence: Level III, cross-sectional study.